2009
DOI: 10.1097/shk.0b013e31819e2d13
|View full text |Cite
|
Sign up to set email alerts
|

Transient Central Cholinergic Activation Enhances Sympathetic Nervous System Activity but Does Not Improve Hemorrhage-Induced Hypotension in Alcohol-Intoxicated Rodents

Abstract: Morbidity and mortality following traumatic injury and hemorrhagic shock is exacerbated in the alcohol-intoxicated individual. The level of hypotension at the time of admittance into the emergency department is a critical indicator of outcome from injury. Previously we have demonstrated that acute alcohol intoxication (AAI) decreases basal mean arterial blood pressure (MABP), exaggerates hypotension throughout hemorrhagic shock (HS), and attenuates the pressor response to fluid resuscitation (FR) in male roden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…This activation was evidenced by increases in circulating levels of counter-regulatory hormones such as AVP and epinephrine as well as enhanced blood pressure following a range of cardiovascular challenges (67, 68). As had been reported in other models, intracerebroventricular (ICV) administration of choline, a pre-cursor of acetylcholine, produced an immediate activation of the SNS as evidenced by an increase in MABP and a rise in plasma epinephrine, norepinephrine, and AVP within five minutes of injection in dextrose control animals (69). While we confirmed that SNS activation could be achieved with this approach, ICV choline did not reverse the hemorrhage-induced hypotension or produce a sustained increase in vasoactive hormone release throughout the duration of hemorrhage in AAI animals.…”
Section: Acute Alcohol Intoxication Disrupts Central Avp Controlling mentioning
confidence: 54%
“…This activation was evidenced by increases in circulating levels of counter-regulatory hormones such as AVP and epinephrine as well as enhanced blood pressure following a range of cardiovascular challenges (67, 68). As had been reported in other models, intracerebroventricular (ICV) administration of choline, a pre-cursor of acetylcholine, produced an immediate activation of the SNS as evidenced by an increase in MABP and a rise in plasma epinephrine, norepinephrine, and AVP within five minutes of injection in dextrose control animals (69). While we confirmed that SNS activation could be achieved with this approach, ICV choline did not reverse the hemorrhage-induced hypotension or produce a sustained increase in vasoactive hormone release throughout the duration of hemorrhage in AAI animals.…”
Section: Acute Alcohol Intoxication Disrupts Central Avp Controlling mentioning
confidence: 54%
“…The results from recent studies demonstrated that intracerebroventricular (ICV) administration of choline, a precursor of acetylcholine, immediately stimulates sympathetic nervous system (SNS) outflow in control and alcohol-intoxicated animals, reflected in an increase in MABP and plasma epinephrine, norepinephrine, and AVP (26). However, these effects were transient and not prolonged enough to improve hemodynamic stability following hemorrhagic shock in alcohol-intoxicated animals.…”
mentioning
confidence: 93%
“…Alcohol-intoxicated trauma patients enter the emergency department more hypotensive than their sober counterparts (41). Clinical data suggest that mean arterial blood pressure (MABP) at the time of admittance into the emergency department is one of the most critical indicators of a patient's outcome and survival from traumatic injury and blood loss (15); therefore, the greater hypotension noted in alcohol-intoxicated trauma patients is likely to contribute to their increased morbidity and mortality.Previously, we demonstrated that acute intoxication produced by intragastric administration of alcohol decreases baseline MABP, accentuates hypotension throughout hemorrhage, and blunts the pressor response to fluid resuscitation, regardless of the dose (1.75, 5, and 8 g/kg) and frequency (single dose, 3-day binge, and 15-h constant infusion, respectively) of alcohol administration (12,25,26,30,33). This impaired hemodynamic compensatory response to hemorrhage in alcohol-intoxicated rats is associated with suppression of catecholamine (epinephrine and norepinephrine) and AVP responses (30).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Investigations into the mechanism of this impaired counterregulatory response have ruled out impaired vascular pressor response as a primary mechanism for the greater hypotension following blood loss observed in the intoxicated host (7). In contrast, studies examining the role of the blunted sympathetic response to hemorrhage have provided strong support for the hypothesis that the impaired response to blood loss during AAI is due to central alterations in sympathetic outflow (8, 9). Central administration of acetylcholinesterase inhibitors increases sympathetic outflow, significantly improves the blunted counterregulatory hormone response associated with AAI, and contributes to an enhanced blood pressure recovery following hemorrhage (8).…”
Section: Introductionmentioning
confidence: 99%